2020
DOI: 10.2337/db19-1231
|View full text |Cite
|
Sign up to set email alerts
|

A TRAIL-TL1A Paracrine Network Involving Adipocytes, Macrophages, and Lymphocytes Induces Adipose Tissue Dysfunction Downstream of E2F1 in Human Obesity

Abstract: Elevated expression of E2F1 in adipocyte fraction of human visceral adipose tissue (hVAT) associates with a poor cardiometabolic profile. We hypothesized that beyond directly activating autophagy and MAP3K5 (ASK)–MAP kinase signaling, E2F1 governs a distinct transcriptome that contributes to adipose tissue and metabolic dysfunction in obesity. We performed RNA sequencing of hVAT samples from age-, sex-, and BMI-matched patients, all obese, whose visceral E2F1 protein expression was either high (E2F1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 49 publications
(77 reference statements)
2
22
0
Order By: Relevance
“…They did however resemble adipose tissue macrophages in several respects(Frey and Vogel, 2011; Li et al, 2020), including activity of the TRAIL pathway ( Fig. 4E ) (Maixner et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…They did however resemble adipose tissue macrophages in several respects(Frey and Vogel, 2011; Li et al, 2020), including activity of the TRAIL pathway ( Fig. 4E ) (Maixner et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that TL1A can regulate metabolism [8,16] in physiological status and play an important role in the modulation of vascular homeostasis and autoimmune diseases [5,7] . The pathogenesis of KD is well known as in ammation and imbalance of immunology resulting in vascular lesion.…”
Section: Discussionmentioning
confidence: 99%
“…TL1A is primarily produced by endothelial cells under stimulation of TNF-α and IL-1, and is also expressed in the lymphocytes, macrophages, dendritic cells, chondrocytes and synovial cells [6] . TL1A could stimulate T cell activation, proliferation, and production of large amounts of essential cytokines via death receptor 3 (DR3), which is expressed mainly on lymphocytes [5] .TL1A plays an important role in apoptosis, modulation of immune responses, vascular homeostasis, glucose and lipid metabolism [5,7,8] . McLaren et al [9] have demonstrated that TL1A promotes the formation of foam cell in vitro by regulating the levels of low-density lipoprotein and cholesterol that are involved in atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…DR3 stimulation also provides a more significant activation of human ILC2s in comparison to GITR ( 28 ). Recently, it was found that human cells from stromal cell vascular fractions in adipose tissue induced TL1A expression in response to TNF-related apoptosis-inducing ligand (TRAIL) significantly more in comparison to other cell types ( 145 ). TRAIL is commonly associated with a variety of obesity-related diseases and plays a role in human adipocyte inflammation ( 146 ).…”
Section: Regulators Of Adipose Ilc2smentioning
confidence: 99%